Spatio-Temporal Analysis Of Yogyakarta Internasional Airport Development Impact On LULC And LST In Kulon Progo - Jauhari, Agung; Setyo Aji, Dwi; Kio Hafidz, Ilham; Rizka Novareka, Aldea; Ajeng Oktaviani, Dwika; Rico Oktavian, Aditya (Pendidikan Geografi Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Yogyakarta Internasional Airport (YIA) development is predicted to trigger massive development in Kulon Progo Regency, whether for the infrastructure or supporting facilities development. Land conversion from densely vegetated land into less dense vegetated land, i.e., forest or garden to built-up areas, is determined to increase Land Surface Temperature (LST). This research studied the spatiotemporal change of LULC and LST change in Kulon Progo Regency by employing Landsat 8 data for three periods respectively, before the development (2013), at the start of construction (2017), and after the YIA fully operated (2021). The spatial pattern of LST was also investigated using spatial statistics, namely, Global Moran’s I, to identify spatial autocorrelation and Hot Spots Analysis (Getis-Ord G*) to determine the spatial patterns or clusters. The findings showed that since the YIA development, the built-up area and bare land increased significantly (quadruple), while agriculture reduced dramatically by 14%. Furthermore, the LST was closely related to the LULC, where the high LST was located in the built-up area and bare land (32 ºC -38ºC), while the low LST was located in the forest (27ºC-31ºC). Moran’s I index, around 0.9 (close to 1), indicates a positive spatial autocorrelation, while the p-value (0.00) indicates that the LST was significantly clustered. Indeed, Hot Spot Analysis (Getis-Ord Gi*) revealed that the high-temperature areas clustered (hot spot) along the coastal and urban areas, while low-temperature areas clustered around Menoreh Hills.